Lower Oxytocin Plasma Levels in Borderline Patients with Unresolved Attachment Representations - Jobst, Andrea; Padberg, Frank; Mauer, Maria-Christine; Daltrozzo, Tanja; Bauriedl-Schmidt, Christine; Sabass, Lena; Sarubin, Nina; Falkai, Peter; Renneberg, Babette; Zill, Peter; Gander, Manuela; Buchheim, Anna (Frontiers in Human Neuroscience, 2016)
Interpersonal problems and affective dysregulation are core characteristics of borderline personality disorder (BPD). BPD patients predominantly show unresolved attachment representations. The oxytocin (OT) system is associated with human social attachment and affiliative behavior, and OT dysregulation may be related to distinct attachment characteristics. Here, we investigated whether attachment representations are related to peripheral OT levels in BPD patients. Twenty-one female BPD patients and 20 age-, gender-, and education-matched healthy controls were assessed with clinical scales and measures of interpersonal and attachment-related characteristics, including the Adult Attachment Projective Picture System (AAP). Plasma OT concentrations were measured prior to and during social exclusion in a virtual ball tossing game (Cyberball). The majority of BPD patients (63.2%) but no healthy controls showed unresolved (disorganized) attachment representations. In this subgroup of patients, baseline OT plasma levels were significantly lower than in BPD patients with organized attachment representations. This pilot study extends previous findings of altered OT regulation in BPD as a putative key mechanism underlying interpersonal dysregulation. Our results provide first evidence that altered OT plasma levels are related to disorganized attachment representations in BPD patients.